2017
DOI: 10.1002/jssc.201700184
|View full text |Cite|
|
Sign up to set email alerts
|

Chromatographic analysis of tryptophan metabolites

Abstract: The kynurenine pathway generates multiple tryptophan metabolites called collectively kynurenines and leads to formation of the enzyme cofactor nicotinamide adenine dinucleotide. The first step in this pathway is tryptophan degradation, initiated by the rate‐limiting enzymes indoleamine 2,3‐dioxygenase, or tryptophan 2,3‐dioxygenase, depending on the tissue. The balanced kynurenine metabolism, which has been a subject of multiple studies in last decades, plays an important role in several physiological and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 159 publications
(466 reference statements)
0
72
0
5
Order By: Relevance
“…Several methods for the analyses of Trp metabolites in plasma and tissue [17,18], in serum [19,20], in urine [9,18,20], in cerebrospinal fluid [17,19] and in cellular media [20,21] have been described [10]. However, the majority of these methods used a triple quadrupole mass spectrometer.…”
Section: Methods Development and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods for the analyses of Trp metabolites in plasma and tissue [17,18], in serum [19,20], in urine [9,18,20], in cerebrospinal fluid [17,19] and in cellular media [20,21] have been described [10]. However, the majority of these methods used a triple quadrupole mass spectrometer.…”
Section: Methods Development and Optimizationmentioning
confidence: 99%
“…A number of studies have reported methods [9][10][11][12][13] for assaying certain Trp metabolites but were all dedicated to discrete physiological compartments. To broaden Trp metabolite assaying from a separate to a connected approach, we sought to develop a new method for the simultaneous quantification of Trp metabolites in different physiological compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Some substances that form the amino acid metabolism can overcome the hematoencephalic barrier and have a direct effect on the brain (Figure 7) [14, [44][45][46]. A search for such low-molecular compounds, quantitative determination, and their ratios can serve as the basis for the development of methods for early diagnosis, including cognitive and mental disorders [47]. It is important to note that metabolites can directly enter the region of the medulla, with blood through arteria vertebralisarteria spinalis, bypassing the hemato-encephalic barrier, and that critical vital centers of respiration and circulation are located there.…”
Section: Neurological Pathology and Mental Disordersmentioning
confidence: 99%
“…Recently, a special attention has been paid to the KP in neuroscience research, especially in light of the well documented alterations of the pathway in numerous neurological disorders, such as Parkinson's disease, Alzheimer's disease, multiple sclerosis and schizophrenia [2][3][4][5][6]. Accordingly, several methods have been developed for the quantification of TRP and its metabolites, including those with multiple-step sample preparation, pre-or post-column derivatization or those needing complex instrumental background (e.g., high-performance liquid chromatography (HPLC) mass spectrometry, gas chromatography mass spectrometry) [7]. The assessment of TRP, KYN and kynurenic acid (KYNA), usually designated as the neuroprotective branch of the KP, may yield meaningful information in several preclinical and clinical studies [1].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of TRP, KYN and kynurenic acid (KYNA), usually designated as the neuroprotective branch of the KP, may yield meaningful information in several preclinical and clinical studies [1]. The detection and quantification of these metabolites can be achieved in an easier way compared to the other compounds of the KP [7][8][9]. The partial assessment of the KP has been described with different HPLC methods, using several detection techniques, including UV detector (UVD) and fluorescence detector (FLD) [9,10], diode array detector [11], electrochemical detector [12] or mass spectrometry [13,14], targeting different biological matrices: human serum or plasma, and cerebrospinal fluid (CSF) [5,[13][14][15][16], murine serum or plasma [9,14], and brain [9,17].…”
Section: Introductionmentioning
confidence: 99%